AI for medical devices - Gliklich, Richard E. (Henry Stewart Talks, 2022)
Artificial intelligence, AI in healthcare, Shared decision-making, Value-based care, Patient identification, Personalized healthcare, Patient Finder, OM1 Medical Burden Index (OMBI), OMBI Score